2020
DOI: 10.1016/j.jaci.2019.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Emerging therapies for eosinophilic esophagitis

Abstract: Despite advances in the pathologic understanding of eosinophilic esophagitis (EoE), as of yet, no single agent has been approved by the US Food and Drug Administration to treat EoE. Off-label, EoE is currently treated by using the 3 Ds: drugs (particularly swallowed topical corticosteroids), dietary restriction, and endoscopic dilation. In the recent past, considerable progress in terms of EoE treatment has been made: (1) new EoE-specific steroid formulations optimizing mucosal deposition have been developed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 63 publications
0
45
0
3
Order By: Relevance
“…Clinical trials of biologic agents that target IL-5 and IL-13 have demonstrated significant histologic improvement but only limited symptomatic benefit for patients with EoE, [11][12][13] and agents targeting tumor necrosis factor-a and IgE do not appear to be effective EoE treatments. 13 Among the most promising biologic agents for EoE is dupilumab, a fully humanized monoclonal antibody directed against the IL-4 receptor-a (IL4Ra) through which both IL-4 and IL-13 signal to increase eotaxin-3 production by esophageal squamous cells. 14,15 In a multicenter, randomized, placebo-controlled phase 2 study, dupilumab demonstrated significant efficacy in improving both clinical and histopathologic features of EoE.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Clinical trials of biologic agents that target IL-5 and IL-13 have demonstrated significant histologic improvement but only limited symptomatic benefit for patients with EoE, [11][12][13] and agents targeting tumor necrosis factor-a and IgE do not appear to be effective EoE treatments. 13 Among the most promising biologic agents for EoE is dupilumab, a fully humanized monoclonal antibody directed against the IL-4 receptor-a (IL4Ra) through which both IL-4 and IL-13 signal to increase eotaxin-3 production by esophageal squamous cells. 14,15 In a multicenter, randomized, placebo-controlled phase 2 study, dupilumab demonstrated significant efficacy in improving both clinical and histopathologic features of EoE.…”
Section: Background and Aimsmentioning
confidence: 99%
“…The major outcome is the presence of Th2 lymphocytes with barrier dysregulation 132 . Major cytokines involved in the pathogenesis of eosinophilic esophagitis such as IL‐4, IL‐5, IL‐13, and TNF have been tested for the treatment of eosinophilic esophagitits 133 . Along with Th2 cytokines, TGF‐β is the major cytokine that mediates lamina propria remodeling in eosinophilic esophagitis 134 .…”
Section: Tight Junction In Eosinophilic Esophagitismentioning
confidence: 99%
“…The dilate and wait strategy was also safe and provided a bridge to clinical trials with novel treatments in almost half of patients. Given the rapidity with which new treatments for EoE are being developed [30], as well as the sizable proportion of EoE patients who are nonresponsive to first-line treatment options [31], this approach is reasonable in these patients who might ultimately benefit from new therapies [25].…”
Section: Discussionmentioning
confidence: 99%